Using musculoskeletal modelling to estimate knee joint loading pre and post high tibial osteotomy. (January 2023) - Bowd, Jake; Van Rossom, Sam; Williams, David; Elson, David; Wilson, Chris; Whatling, Gemma; Holt, Cathy; Jonkers, Ilse
Abstract: Background: Both medial knee osteoarthritis and associated varus alignment have been proposed to alter knee joint loading and consequently overloading the medial compartment. Individuals with knee osteoarthritis and varus deformity are candidates for coronal plane corrective surgery, high tibial osteotomy. This study evaluated knee loading and contact location for a control group, a pre-surgery cohort and the same cohort 12 months post-surgery using a musculoskeletal modelling approach. Methods: Joint kinematics during gait were measured in 30 knee osteoarthritis patients, before and after high tibial osteotomy, and 28 healthy adults. Using a musculoskeletal model that incorporated patient-specific mechanical tibial femoral angle, the resulting muscle, ligament, and contact forces were calculated and the medial - lateral condyle load distribution was analysed. Findings: Surgery changed medial compartment contact force throughout stance relative to pre-surgery. This reduction in medial compartment contact force pre- vs post-HTO is observed despite a significant increase in post-surgery walking speed compared to pre-HTO, where increased speed is typically associated with increased joint loading. Interpretation: This study has estimated the effects of high tibial osteotomy on knee loading using a generic model that incorporates a detailed knee model to better understand tibiofemoral contact loading. The findings support the aim of surgery to unload the medial knee compartment and lateralise joint contact forces. Highlights: Contact forces. Malalignment. Varus. High tibial osteotomy. Osteoarthritis.